Reactions between the liquid alkali-metals and liquid water - Ashworth, Allan B. (1979)
The rates of reaction of the constituents of sodium-potassium alloy with water have been determined in the temperature range 20 - 600C. They fall into two categories; the first is applicable to the instant the alloy meets the water, and the second applies to reaction of the metal through a bubble of hydrogen. The rates are widely different for these two stages, yet the activation energies are similar, being 38.3 and 33.0 KJ/mole respectively for sodium, and 24.5 and 27.3 KJ/mole respectively for potassium. The rate of reaction of sodium alone at 30 C, has also been determined.